EFL Students' Perceptions on the Integration of AI in Fostering Critical Thinking Skills - Eka Fatmawati Hading; Dwi Rezki Hardianto Putra Rustan; Fentry Hernaningsi Ruing (PT. Global Research Collaboration, 2024)
A developing discussion over the effects of Artificial Intelligence (AI) on students' critical thinking skills has emerged with their introduction into the classroom. Even if AI can provide several advantages, some worries depending too much on these technologies could impede the growth of critical thinking abilities. This research aims to analyze how students perceive the influence of AI on their critical thinking abilities. This research is descriptive qualitative research that involves collecting data from direct interviews. The respondents are 15 (fifteen) students from the English Literature study program, Letter Faculty, Sawerigading University Makassar. The research found that students perceive the following impact of AI use on their critical thinking abilities: 1) Hindering the development of critical thinking skills. 2) Assisting in the retrieval of information, data analysis, and the resolution of everyday issues. 3) Causing dependence on technology. 4) Helping to evaluate the information quickly; 5) Exploring alternative ideas; and 6) Improving reasoning ability. Overall, we need to balance the use of AI while prioritizing students' critical thinking. It is important to encourage students to use AI responsibly and judiciously, while also emphasizing the importance of critically evaluating the information provided by AI systems.